Multiquartic functional equations - Abasalt Bodaghi; Choonkil Park; Oluwatosin T. Mewomo (Advances in Difference Equations, 2019)
Abstract In this paper, we study n-variable mappings that are quartic in each variable. We show that the conditions defining such mappings can be unified in a single functional equation. Furthermore, we apply an alternative fixed point method to prove the Hyers–Ulam stability for the multiquartic functional equations in the normed spaces. We also prove that under some mild conditions, every approximately multiquartic mapping is a multiquartic mapping.